Family Beyond Boundaries: A Case Insight Into Islamic Extended Family Dynamics - Muhamad Rafiqi Hehsan; Nathratul Ayeshah Zulkifli; Zulkifli Dahalan (Human Resource Management Academic Research Society, 2025)
Indexed by ERA